2018
DOI: 10.3847/1538-4357/aae1f7
|View full text |Cite
|
Sign up to set email alerts
|

The VLA/ALMA Nascent Disk and Multiplicity (VANDAM) Survey of Perseus Protostars. VI. Characterizing the Formation Mechanism for Close Multiple Systems

Abstract: We present Atacama Large Millimeter/submillimeter Array (ALMA) observations of multiple protostar systems in the Perseus molecular cloud previously detected by the Karl G. Jansky Very Large Array (VLA). We observed 17 close (<600 AU separation) multiple systems at 1.3 mm in continuum and five molecular lines (i.e., 12 CO, C 18 O, 13 CO, H 2 CO, SO) to characterize the circum-multiple environments in which these systems are forming. We detect at least one component in the continuum for the 17 multiple systems. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 79 publications
14
73
0
Order By: Relevance
“…Per-emb 17 is a close binary system with a separation of 0 278 ± 0 014 (83.3 ± 4.0 au with a distance of 300 pc; Tobin et al 2018). Our observations show clear double-peaked features for most of the emission (Figure 9).…”
Section: The Double-peaked Features Of Per-emb 17mentioning
confidence: 59%
See 1 more Smart Citation
“…Per-emb 17 is a close binary system with a separation of 0 278 ± 0 014 (83.3 ± 4.0 au with a distance of 300 pc; Tobin et al 2018). Our observations show clear double-peaked features for most of the emission (Figure 9).…”
Section: The Double-peaked Features Of Per-emb 17mentioning
confidence: 59%
“…B5 has a dominant embedded protostar, IRS1, along with three gravitationally bound gas condensation at a separation greater than 1000 au (Pineda et al 2015). Furthermore, the protostellar multiplicity in Perseus has been extensively studied by the VLA Nascent Disk and Multiplicity Survey (VANDAM) of Perseus protostars, showing a multiplicity fraction of 0.57 ± 0.09 and 0.23 ± 0.08 for Class 0 and I protostars, respectively (Tobin et al 2016(Tobin et al , 2018Segura-Cox et al 2018;Tychoniec et al 2018). Murillo et al (2016) further characterized the spectral energy distributions of all sources identified in the VANDAM survey to derive protostellar properties, such as bolometric luminosities (L bol ), bolometric temperatures (T bol ), and evolutionary stage classification.…”
Section: Introductionmentioning
confidence: 99%
“…The VLA Nascent Disk and Multiplicity Survey of Perseus Protostars (VANDAM) by Tobin et al (2016b) found a bimodality in the multiplicity of systems; they argued that the wide multiples are the result of turbulent fragmentation, whereas the tight multiples are the result of disk fragmentation. This latter conclusion was strengthened in a follow-up study by Tobin et al (2018), who observed a sample of tight binaries from the VANDAM survey with ALMA in both continuum and spectral lines.…”
Section: Misalignment Of Outflows and Magnetic Fieldsmentioning
confidence: 86%
“…The contours in the right panel of Figure 1 also show the binary companion (L1448 IRS 2B), which is separated from the primary by about 0 6 (corresponding to ∼180 au at the target distance) toward the west. This companion is less bright in the 1 mm continuum and has been detected at 9 mm (Ka-band; Tobin et al 2016) and at 1 mm (Tobin et al 2018). The blue and red contours overlaid in the figure are CO 2-1 molecular line data taken by ALMA (2013.1.00031.S; Tobin et al 2018).…”
Section: Magnetic Field Morphologymentioning
confidence: 92%